Biomechanical effects of daily physical activities on the lower limb - Serbest, Kasım (Acta orthopaedica et traumatologica turcica, 2015)
The aim of this study was to determine the joint torques on the lower extremity during the daily physical activity movements of sit-to-stand, crouch down-stand up, and stair climbing without using an external device. The study subject was a healthy 26-year-old male without any physical problems. A link-segment model was prepared according to the subject's individual anthropometric characteristics and transferred to the MATLAB(®) program. Joint torques were calculated using SimMechanics™ software. Motions were recorded by one digital video camera as the subject performed the movements (sit-to-stand from 20 cm and 40 cm height, crouch down-stand up, and climbing 10 cm and 20 cm high step) and the joint's position data was obtained using a digitization process. In addition, the vertical ground reaction forces were measured using a force plate in order to test the accuracy of the link-segment model. Lower extremity joint torques were calculated. Maximum joint torques occurred in the knee joint. The knee and the ankle joints were the most loaded joint during the high step movement. The highest torques of the knee and ankle joint were 157.2 Nm and 146 Nm, respectively, during the movements. Knee joint torque and the ankle joint torque increased when the sitting height increased. The hip joint experienced the least amount of load during the movements. The knee joint has enough strength against high torques during extension and flexion movement. Joint torques can be successfully calculated using a simulation process involving an inverse dynamics method without an external device mounted on the limbs. The obtained data can be used in the design of prosthetics and orthotics and for structural analysis of the bones.